Recent developments in applied microbiology and biochemistry - Viswanath, Buddolla (Academic Press, an imprint of Elsevier, 2019)
"Touching all areas of microbiology, Recent Developments in Applied Microbiology and Biochemistry provides understanding to the application-oriented microbial concepts and updates the knowledge with recent developments on related aspects of both microbial biotechnology and medical, agricultural and environmental microbiology."--Book cover